Answer:
H. 2
Step-by-step explanation:
√(1 − cos² x) / sin x + √(1 − sin² x) / cos x
Use Pythagorean identity.
sin² x + cos² x = 1
So:
1 − cos² x = sin² x
and
1 − sin² x = cos² x
Substitute:
√(sin² x) / sin x + √(cos² x) / cos x
sin x / sin x + cos x / cos x
1 + 1
2
Answer:
See below
Step-by-step explanation:
a = 15 sqrt 2 sin 45
= 15 sqrt 2 * sqrt( 2 ) /2 = 15 * 2 /2 = 15
sin 60 = a/c
sqrt(3)/2 = 15/c
c = 15 / ( sqrt(3)/2) = 30 / sqrt 3 = 30 sqrt 3 /3 = 10 sqrt 3
Answer:
(x-8)(x+3)
Step-by-step explanation:
1) Find out what are the factors of the constant?
2) Which of those add to equal the coefficient before the x value?
In this particular equation, we have the constant being 24. The first two factors that come to mind are 6 and 4, and 8 and 3. Since it is -24, we need one of these numbers to be negative.
Let's look at our "b" value, or the coefficient behind the x value, 5. Looking at our factors and thinking of addition (since one of them must be negative, it will most likely be subtraction instead of addition) I can see that
8+ −3=5
which is one of the factors of -24.
This means that we can factor our equation using these numbers, getting us the following:
(x−3)(x+8)
Hope this helped!
15 and one half is 31/2. 3 and seven eighths is 31/8. 31/2 also equals 124/8. Then the answer is 124/8 - 31/8 is 91/8. Hope that helped.